Structural, optical, and nuclear magnetic resonance studies of V2O5-doped lead calcium titanate borosilicate glasses. (March 2019) - Das, Sangeeta; Madheshiya, Abhishek; Ghosh, Manasi; Dey, Krishna Kishor; Gautam, Satyam Shivam; Singh, Jai; Mishra, Ramanuj; Gautam, Chandkiram
Abstract: In this study, the melt-quenching technique was used to synthesize various glass compositions for the system 55[(Pbx Ca1-x )·OTiO2 ]-44[2SiO2 ·B2 O3 ]-1V2 O5 (0.0 ≤ x ≤ 0.7). The synthesized glasses were investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, ultraviolet–visible spectroscopy, scanning electron microscopy (SEM), and nuclear magnetic resonance spectroscopy (NMR). The experimental density of the glass samples increased from 1.48 to 2.19 g/cm 3 as the concentration of lead oxide (PbO) increased. The XRD results agreed well with the SEM observations and they confirmed the amorphous nature of the glasses. The FTIR and Raman analyses indicated the presence of various bonds comprising VOV, PbOB, BOB, SiOSi, BOSi and BOH, which were attributed to different vibrations. The optical band gap values decreased from 2.07 to 1.65 eV as the PbO content increased. 29 Si and 11 B magic angle spinning solid state NMR spectral analysis suggested that the number of non-bridging oxygens increased within the silicate and borate network as the concentration of PbO increased in the glassy system. Highlights: Glasses synthesized for 55[(Pbx Ca1-x )·OTiO2 ]-44[2SiO2 ·B2 O3 ]-1V2 O5 (0.0 ≤ x ≤ 0.7). Changes in CaO and PbO increased the density and decreased the molar volume. Vibrational bonds comprising VOV, PbOB, BOB, SiOSi, BOSi, and BOH detected. Energy band gap values decreased as PbO concentration increased. Three-coordinated boron dominated tetrahedral boron as PbO concentration increased.